Evaluasi Efektivitas Lapisan Area Penimbunan Faba dalam Pengendalian Kualitas Air Tanah di Sumur Pantau PT. PLN Nusantara Power UP Paiton - Andini Virgiana Rahmawati; Restu Hikmah Ayu Murti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Fly ash and bottom ash (FABA) are combustion residues from coal-fired power plants. Following the issuance of Government Regulation No. 22 of 2021, FABA is no longer classified as hazardous and toxic waste (B3). However, FABA must still be managed properly due to its potential to cause pollution through leachate generated if leaks occur in the FABA disposal area. This study evaluates the lining and drainage systems in the FABA disposal area at PT. PLN Nusantara Power UP Paiton to ensure that leachate does not contaminate surrounding groundwater. The research employs descriptive qualitative and quantitative methods, collecting secondary data to assess the structure and pollution control systems in the FABA disposal area at PT. PLN Nusantara Power UP Paiton. The data includes the disposal area structure and water quality from monitoring wells. Analysis results indicate that the FABA disposal area lining system operates effectively and in compliance with regulations, successfully containing leachate movement and preventing seepage. This is supported by pH, Fe, Hg, and turbidity levels in groundwater from monitoring wells remaining within safe limits. Additionally, the presence of a runoff pond helps contain surface runoff during heavy rain, keeping overflow water under control. Overall, the disposal area structure and leachate management system at PT. PLN Nusantara Power UP Paiton function well, but routine monitoring must continue to ensure no seepage occurs, preventing leachate from contaminating the surrounding environment as an early preventive measure to maintain environmental quality and regulatory compliance.